Systematic review: Association between gut microbiota and mental health (International Seven Journal of Health Research, 2024)
Depression and anxiety, characterized today by many as the disease of the century, represent a serious public health problem. The intestinal microbiota, on the other hand, consists of the set of microorganisms that have the human intestine as their natural biological habitat and that is responsible for several functions, being essential for the maintenance of homeostasis and is in communication with the central nervous system through the intestine-brain axis. With some alterations that may happen in this communication, they may have a direct relationship with mental pathologies, such as anxiety and depression.